Analysis of the state of preservation the historic arcaded houses in Vistula Delta listed in the National Inventory of Historical Monuments - Tomasz Zybala (Lublin University of Technology, 2021)
Historic arcaded houses are part of the material heritage of the Vistula  Delta. Unfortunately, their number is decreasing year by year. The article is the result of a query of available sources and field research carried out by the author in 2015-2020. The paper presents the current state of preservation the historic arcaded houses in Vistula Delta listed in the National Inventory of Historical Monuments. Criteria for the selection of test objects are described. The author has prepared a tabular list of arcaded houses with information about their location, type according to Kloeppel statistics, date of construction, technical condition and functions. The summary of the analysis are pie charts with a statistical presentation of the data collected by the author during the research.